Structural and magnetic properties of Fe1−xCoxSe1.09 nanoparticles obtained by thermal decomposition. (14th December 2015) - Li, Oksana A; Lin, Chun-Rong; Chen, Hung-Yi; Hsu, Hua-Shu; Wu, Kai-Wun; Tseng, Yaw-Teng; Bayukov, Oleg A; Edelman, Irina S; Ovchinnikov, Sergey G; Shih, Kun-Yauh
Abstract: A series of Fe1− x Cox Se1.09 ( x  = 0 to 1) nanoparticles were synthesized by thermal decomposition method. Particles in composition range Fe0.5 Co0.5 Se1.09 to CoSe1.09 crystallized in monoclinic structure of Co6.8 Se8, while FeSe1.09 crystallized in hexagonal structure of FeSe achavalite. Magnetization dependences on temperature and external magnetic field reveal complicated magnetic behavior and correspond to the sum of paramagnetic and superparamagnetic response. Mössbauer spectra contain several paramagnetic doublets with parameters corresponding to nonequivalent positions of divalent and trivalent iron cations with low spin. The nonequivalent positions appeared due to inhomogeneous distribution of Co ions or metal vacancies in iron surrounding.